Installation and calibration of sensors for analysis of soil humidity and temperature in eastern Amazon areas - Silva Junior, Renato; Tavares, Alexandra Lima; Silva, Marcio Sousa da; Martins, Gabriel Caixeta; Costa, Carlos Eduardo Aguiar de Souza; Melo, Adayana Maria Queiroz de; Nascimento Júnior, Wilson da Rocha (Journal of Environmental Analysis and Progress, 2023)
Soil moisture and temperature are important components to improve watershed management and natural resource planning. In that way, this article aimed to evaluate the installation and calibration of five sensors (Drill & Drop) as well as the consistency of the results obtained for moisture and soil temperature in areas of forest, pasture, forest-pasture transition, and pasture-urban transition in the Itacaiúnas River Hydrographic Area (IRB) in the Eastern Amazon. The results are from April to September 2019, showing different trends between forest and pasture areas. The data consistency analysis efficiently identified measurement errors, especially in the soil’s surface layer (10 cm). The highest percentage of error data occurred in the Onça Puma and IFPA rural stations, with 22.8% and 17.6%. On the other hand, these results may be associated with the environmental characteristics of the region, as well as the soil’s physical characteristics during each season. The soil temperature and humidity parameters were consistent with data from other meteorological variables (precipitation and mean air temperature) measured by sensors installed in the local hydrometeorological stations. Generally, the temperature and soil moisture measurements were obtained properly and are presented as quality data sources. Thus, it is expected that the results will contribute to enriching the availability of soil data in the IRB and encourage the use of direct measurements given the quantity (and quality) of data obtained using this instrumentation.